Learner-Centered Teaching Practices and Classroom Engagement at Baluarte Elementary School: A Qualitative Institutional Study - GRANIL, CHRISTOPHER (Studies in Technology and Education, 2025)
Learner-centered pedagogy has gained prominence in basic education as an approach that promotes active participation, meaningful learning, and holistic learner development. While policy frameworks strongly advocate learner-centered teaching, empirical evidence documenting how such practices are enacted at the classroom level particularly in elementary school contexts remains limited. This qualitative institutional study explored learner-centered teaching practices and their influence on classroom engagement at Baluarte Elementary School. Using classroom observations, semi-structured teacher interviews, and focus group discussions with learners, the study examined how instructional strategies, classroom interactions, and learning environments shaped behavioral, emotional, and cognitive engagement. Thematic analysis revealed four major themes: (1) active learning through participatory instructional strategies, (2) differentiated and contextualized instruction supporting learner engagement, (3) supportive classroom relationships fostering confidence and participation, and (4) contextual constraints shaping the enactment of learner-centered practices. Findings indicate that learner-centered teaching practices substantially enhanced learners’ engagement by promoting autonomy, relevance, and social interaction. However, challenges related to class size, instructional resources, and teacher workload influenced consistency of implementation. The study underscores the importance of institutional support and professional development in sustaining learner-centered pedagogy in elementary education.